Analysis and design of an open channel flow flume : reservoir section - Muhammad Adlin, Hasmar (2013)
The facilities for testing hydro turbine is not many in Malaysia, hence flume project is initialize to overcome this problem. This study is about on choosing the best reservoir designs that need to be implement in flume project, to choose the best the design, there are analysis that need to be done, stress and strain analysis, CFD analysis and costing analysis also should be include. Throughout the analysis, the main parameter of choosing reservoir design can be recognize, in this study there are two main parameters for choosing the best tank design that is, pressure drop and costing. The need of reservoir generally in term of costing for the whole project is because a costly pipe material would be required to withstanding a very high pressure in a very long pipe system. Therefore using reservoir is more economical compare to costly pipeline material, but in term of reservoir costing only, the variable that we can change is the volume of material use and also price of material. The volume of material used is depends on the dimension of the design and the dimension is depends on the criteria that this project need for reservoir section, to reduce volume material used, a single, double, and triple design is rational to be proposed. Choosing a right material need several analysis to be done, firstly throughout the CFD analysis, the data for maximum total pressure across wall can be obtain and with this data, a stress and strain analysis will be perform using a different grade of concrete, in this project the material used is concrete because it cannot be corroded since the fluid medium will be water so corrosion aspect is important. With stress and strain analysis, the maximum deflection data for each design can be obtain, the maximum deflection is like the safety level for the material use, the less deflection the more level of safety of the material, hence an optimum material with less price but strong can be choose, in this study the most suitable material to be use is grade 10 ready mix concrete. For pressure drop factor, it is depends on the design, in this study the design that have been proposed is parshall design, rectangular design and circular design varied with single, double and triple tank. In conclusion the design that full fills this both parameters is double tank parshall design.